Analisis Teknologi Pembelajaran dalam Pendidikan Sekolah Dasar - Devie Anggraeny; Dina Aulia Nurlaili; Rachil Amalia Mufidah (FONDATIA, 2020)
This study aims to find out about the extent to which technology plays a role in the continuity of learning in SDN Karang Tengah 11. And to find out what are the advantages and disadvantages of learning technology in the SDN. The method used in this research is descriptive qualitative method. In education, learning using technology carried out by the teacher is very helpful in the learning process. Especially for elementary school students whose characteristics are still at an early development stage, therefore teachers need to use technology as a learning medium so that students are more interested in participating in learning. Teachers also need to understand about technology in the current era so that teachers in Indonesia are not out of date. From the results of the study it was found that the teachers at SDN Karang Tengah 11 had used technology in learning, such as displaying pictures, films, and others using a projector.